2012
DOI: 10.18359/rcin.246
|View full text |Cite
|
Sign up to set email alerts
|

Estudio comparativo de pastas de cemento adicionadas con catalizador de craqueo catalítico usado (FCC), y metacaolín (MK)

Abstract: <span>Este artículo es parte de un proyecto de investigación cuyo objetivo principal es evaluar el desempeño de un residuo de una refinería de petróleo, como adición al cemento Portland con el fin de establecer la viabilidad de su aplicación en materiales de construcción. Este residuo denominado catalizador usado a partir del proceso de craqueo catalítico (fcc) procede de las unidades de ruptura catalítica en lecho fluido y está compuesto principalmente por sílice y alúmina. Se analizó </span><s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This was due to the high reactivity of the material (Borrachero et al, 2002;Jung-Hsiu et al, 2003;Pacewska et al, 2002a). Similar results have been found by Trochez et al, 2010;Torres et al, 2012b, showing that the residue of the catalytic cracking catalyst presents a high reactivity. This assertion results evident in the consumption of calcium hydroxide, which comes from cement hydration.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This was due to the high reactivity of the material (Borrachero et al, 2002;Jung-Hsiu et al, 2003;Pacewska et al, 2002a). Similar results have been found by Trochez et al, 2010;Torres et al, 2012b, showing that the residue of the catalytic cracking catalyst presents a high reactivity. This assertion results evident in the consumption of calcium hydroxide, which comes from cement hydration.…”
Section: Introductionsupporting
confidence: 73%
“…In contrast, the MK used in this research, is predominantly of amorphous shape, with traces of quartz as the only crystalline phase (Torres et al, 2012a, Torres et al, 2012bTrochez et al, 2010).…”
Section: Torres-castellanos Torres-agredo and Mejía-de-gutierrezmentioning
confidence: 92%
“…the lowest peak intensities were observed in the compositions with a composite pozzolanic additive (C-CMK and CP-CMK). The obtained results could suggest that FCCW not only accelerates early cement hydration [44] but also encourages the formation of hydration products (portlandite) in later cementitious material curing periods. Uniformly distributed fine MK particles in the cementitious material react with portlandite during the pozzolanic reaction to produce products such as C-S-H, C-A-H, and C-S-H and C-A-S-H, the key products of cement hydration, were not identified in any X-ray diffraction curves cement paste composition and curing time (7 and 28 days) due to their amorphous nature [34,[39][40][41].…”
Section: Analysis Of Hydration Products (Xrd and Tg-dtg)mentioning
confidence: 81%
“…A comparison of the portlandite peak intensities of the compositions with aluminosilicate pozzolanic additives only showed that the highest portlandite intensities were recorded in all cases involving compositions with a spent catalyst (C-CW and CP-CW), and the lowest peak intensities were observed in the compositions with a composite pozzolanic additive (C-CMK and CP-CMK). The obtained results could suggest that FCCW not only accelerates early cement hydration [44] but also encourages the formation of hydration products (portlandite) in later cementitious material curing periods. Uniformly distributed fine MK particles in the cementitious material react with portlandite during the pozzolanic reaction to produce products such as C-S- H, C-A-H, and C-A-S-H.…”
Section: Analysis Of Hydration Products (Xrd and Tg-dtg)mentioning
confidence: 81%
“…Thermogravimetric analysis is a more precise technique than XRD analysis to determine the amount of portlandite formed in hardened cement paste. TG-DTG curves of cement specimens after 7 and 28 days of curing are presented in Figures 10 and 11 TG-DTG curves reveal 3 endothermic peaks: the first one (30°C-300°C) is related to the processes that occur in this temperature range, namely evolution of free water (at 30°C-105°C), dehydration of CSH (at 115°C-120°C), ettringite (at 100°C-180°C), CAH and CASH (at 180°C-240°C); the second peak at 430°C~550°C is related to portlandite dissolution; and the third peak at 650°C~750°C is related to decarbonisation process [47][48][49][50]. Table 3 shows portlandite amount evaluation results in the temperature range 450°C-520°C according to Equation 1.…”
Section: Analysis Of Hydration Products (Xrd and Tg Dtg)mentioning
confidence: 99%